Metamaterial with negative refraction over wide frequency band. (August 2014) - Gao, P.; Zhang, C.; Ai, J.; Li, G.; Kang, Y.
<x content-type="archive" xml:space="preserve">Abstract</x> This work presents the measurements of square split resonant rings and metal wires (MWs) and C split resonant rings and MW samples through a prism refraction experiment. Negative refraction properties are observed in both models, and the cell shapes are found to play an important role in resonant frequency of the metamaterial samples. A new method is proposed to strictly broaden the negative refraction passband through overlapping the bandwidths using mixed split resonant rings and MWs. The broadened negative refraction bandwidth over a range of 8–12 GHz wider than the other models is proved by both simulative and experimental results, and provided a good metamaterial property.